Peran Knowledge Management dan Organizational Learning Terhadap Inovasi Produk pada Usaha Kecil Menengah Olahan Pangan di Bogor (Relationship between Knowledge Management (KM) and Organizational Learning (OL), and Their Impacts on Product Innovation in SMEs Food Processing at Bogor) - Irwan Siswanto; M. Syamsul Maarif; Mukhamad Najib (IPB University, 2014)
The purpose of the study is to establish tbe relationship between knowledge management (KM) and organizational learning (OL), and their impacts on product innovation in SMEs food processing. 60 SMEs in food processing industry were selected in Bogor, and structural equation modeling (SEM) SMART PLS was applied to test the hypotheses in this research model. The result showed that the knowledge manangement (KM) and organization learning (OL) have a positive relationship. Knowledge manahement does not have positive effect on product innovation, while the organizational learning gives positive effect on product innovation.Keywords : Knowledge Management, Organizational Learning, Product Innovation, Small Medium Enterprise (SME)